The proton momentum distribution in strongly H-bonded phases of water: A critical test of electrostatic models - Burnham, C. J. (American Institute of Physics, 2011)
Water is often viewed as a collection of monomers interacting electrostatically with each other. We compare the water proton momentum distributions from recent neutron scattering data with those calculated from two electronic structure-based models. We find that below 500 K these electrostatic models, one based on a multipole expansion, which includes the polarizability of the monomers, are not able to even qualitatively account for the sizable vibrational zero-point contribution to the enthalpy of vaporization. This discrepancy is evidence that the change in the proton well upon solvation cannot be entirely explained by electrostatic effects alone, but requires correlations of the electronic states on the molecules involved in the hydrogen bonds to produce the observed softening of the well.